From: Bro 1746/19. Writings of K. Liebknecht: 'Klassenkampf gegen den Krieg!', 'Der Hauptfeind steht im eigenen Land' from the year 1915 and his May 1 leaflet from the year 1916
From: Bro 1746/19. Writings of K. Liebknecht: 'Klassenkampf gegen den Krieg!', 'Der Hauptfeind steht im eigenen Land' from the year 1915 and his May 1 leaflet from the year 1916.